2004
DOI: 10.1115/1.1773588
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Instabilities of Natural Convection Flow in a Vertical Cylinder With Partially Heated Sidewall

Abstract: The three-dimensional axisymmetry-breaking instability of an axisymmetric convective flow in a vertical cylinder with a partially heated sidewall is studied numerically. The central part of the sidewall is maintained at constant temperature, while its upper and lower parts are thermally insulated. The dependence of the critical Grashof number on the cylinder aspect ratio (A=height/radius) is obtained for a fixed value of the Prandtl number, Pr=0.021, and fixed length of the heated central region, equal to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
7
13
0
1
Order By: Relevance
“…As has been shown by Rubinov et al, 11 the flows which will bifurcate from these toroidal flows will break the axisymmetry property. More precisely, they have shown that, depending on the aspect ratio of the cavity, different perturbation modes ͑defined by their azimuthal wave number k͒ are associated with this axisymmetry breaking.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…As has been shown by Rubinov et al, 11 the flows which will bifurcate from these toroidal flows will break the axisymmetry property. More precisely, they have shown that, depending on the aspect ratio of the cavity, different perturbation modes ͑defined by their azimuthal wave number k͒ are associated with this axisymmetry breaking.…”
Section: Resultsmentioning
confidence: 83%
“…The cylinder aspect ratio ͑A = height/ radius͒ ranges from 2 to 8, whereas a fixed Prandtl number, Pr= 0.021, is considered as well as a fixed length of heated zone, equal to the cylinder radius. Our study is a continuation of the work of Rubinov et al: 11 by linear stability analysis, they have determined the thresholds at which the three-dimensional axisymmetry breaking of the flow occurs; by three-dimensional numerical simulation, we will study the three-dimensional patterns appearing beyond these thresholds and their further transitions. A finite volume approach based on the multigrid SIMPLE scheme is used for the computation of steady states, while an improved fractionstep finite-difference method is used for the oscillatory cases.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Details on this problem can be found in [4], where it was studied by the global Galerkin method. The results of [4] were then used in [9,11] as a benchmark data. Here, we consider one particular case defined by A = 2 and Pr = 0.03.…”
Section: Buoyancy Convection In a Cylinder With Parabolically Heated mentioning
confidence: 99%
“…The three dimensional axisymmetry-breaking instability of natural convection in a vertical Bridgman growth configuration with different thermal boundary conditions was studied by Gelfgat's group [6,7]. It was shown that the first instability of the considered flow is always threedimensional.…”
Section: Introductionmentioning
confidence: 99%